Identifying Patients at High Risk of Developing Non-Cirrhotic Portal Hypertension - Gioia S; Riggio O; Nardelli S; d'Amati G; Ridola L (Hepatic Medicine: Evidence and Research, 2021)
Stefania Gioia,1 Oliviero Riggio,1 Silvia Nardelli,1 Giulia d’Amati,2 Lorenzo Ridola1 1Department of Translational and Precision Medicine, Sapienza University of Rome, Rome, Italy; 2Department of Radiological, Oncological, and Pathological Sciences, Sapienza University of Rome, Rome, ItalyCorrespondence: Stefania GioiaDepartment of Translational and Precision Medicine, Sapienza University of Rome, Rome, ItalyTel +39 06 49970463Email stensgioia@hotmail.comAbstract: The term porto-sinusoidal vascular disease (PSVD) has been recently proposed to replace the term idiopathic non-cirrhotic portal hypertension (INCPH) to describe patients with or without signs of portal hypertension and typical histological lesions involving the portal venules or sinusoids in the absence of cirrhosis. According to the new definition, the presence of known causes of liver disease as well as of portal vein thrombosis does not rule out PSVD. Therefore, the patients in whom the diagnosis of PSVD is possible are much more than the patients strictly fulfilling the diagnostic criteria for INCPH. In this setting, the clinical challenge for the hepatologist is to identify patients at risk of developing PSVD and to indicate liver biopsy to confirm the diagnosis. We describe some possible scenarios in which PSVD should always be suspected, and we provide some tools useful to reach the diagnosis of PSVD.Keywords: porto-sinusoidal vascular liver disease, idiopathic non-cirrhotic portal hypertension, portal vein thrombosis, portal hypertension